The Influence of Prefermentation Skin Contact, Stabulation, and Skin Fermentation on the Aromatic Behaviour and Phenolic Compounds of Important Austrian White Wine Cultivars - Christian Philipp; Phillip Eder; Sezer Sari; Karin Korntheuer; Reinhard Eder (Australian Journal of Grape and Wine Research)
Many varietal aromas of wine are located in the berry skin. In the present study, we evaluated four important Austrian grape varieties: Grüner Veltliner, Sauvignon Blanc, Traminer, and Pinot Blanc. We assessed whether prefermentation skin contact, fermentation with the skin (only for Grüner Veltliner), and stabulation (lees stirring; only for Sauvignon Blanc, Traminer, and Pinot Blanc) could enhance the varietal aromas of the different grape cultivars. The aim was to intensify the varietal aromas without extracting the undesirable phenols. We performed a detailed analytical characterisation of approximately 100 volatile and phenolic compounds as well as a sensory characterisation. Although mash fermentation significantly increased the spicy aromas of Grüner Veltliner, which are affected by climate change (especially the sesquiterpene rotundone), it markedly decreased the fruitiness and increased the bitterness; therefore, it cannot be recommended for this cultivar. For Sauvignon Blanc, stabulation is a possible option; the varietal aromas (thiols and methoxypyrazines) were increased in the final wines of these variants. For Pinot Blanc and Traminer, prefermentation skin contact yielded the best results: for Traminer, it produced the highest content of monoterpenes (especially z-rose oxide), and for Pinot Blanc, it produced the highest content of ethyl esters. To summarise, stabulation will not completely replace classic skin contact, and mash fermentation is certainly not an alternative for the production of standard Grüner Veltliner wine. However, additional investigations are necessary with regard to other grape varieties, terroirs, and vintages before we can make final recommendations.